2021
DOI: 10.3390/jcm10245971
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound-Guided Protocol to Confirm Central Venous Catheter Placement in Pediatric Patients Undergoing Cardiothoracic Surgery: A Prospective Feasibility Study

Abstract: Background: Central venous catheters (CVC) are commonly required for pediatric congenital cardiac surgeries. The current standard for verification of CVC positioning following perioperative insertion is postsurgical radiography. However, incorrect positioning may induce serious complications, including pleural and pericardial effusion, arrhythmias, valvular damage, or incorrect drug release, and point of care diagnostic may prevent these serious consequences. Furthermore, pediatric patients with congenital hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The resulting multiple attempts lead to delays in procedural processes and may induce secondary complications such as hematoma or temporary—or even permanent—vascular occlusion with subsequent distal necroses [ 1 , 2 , 8 , 9 ]. Ultrasound guidance for vascular access and regional anesthesia allows for direct visualization of targeted vessels and nerval structures and the puncture process and can provide confirmation of the correct guidewire and catheter positioning, and is therefore established in anesthesia and intensive care medicine and recommended in recent guidelines [ 10 , 11 , 12 , 13 ]. However, in contrast to venous access and nerve blockade, radial artery cannulation is still commonly performed via palpation, and sonography is only used when multiple attempts have failed.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting multiple attempts lead to delays in procedural processes and may induce secondary complications such as hematoma or temporary—or even permanent—vascular occlusion with subsequent distal necroses [ 1 , 2 , 8 , 9 ]. Ultrasound guidance for vascular access and regional anesthesia allows for direct visualization of targeted vessels and nerval structures and the puncture process and can provide confirmation of the correct guidewire and catheter positioning, and is therefore established in anesthesia and intensive care medicine and recommended in recent guidelines [ 10 , 11 , 12 , 13 ]. However, in contrast to venous access and nerve blockade, radial artery cannulation is still commonly performed via palpation, and sonography is only used when multiple attempts have failed.…”
Section: Discussionmentioning
confidence: 99%
“…It provides a new idea and method for selecting the best type of ETT for children. Baehner et al (2021) [13] mentioned in their study that the transverse diameter of the trachea in the strictest subglottic part of children could be individually measured by ultrasound technology. Ponde et al (2021) [14] mentioned that ultrasonic measurement technology can be utilized for guiding the selection of ETT type in children with TI clinically.…”
Section: Backgroudmentioning
confidence: 99%
“…In contrast, the advantage of ultrasound is that it can provide the desired information immediately after catheter insertion. Controlling the catheter position solely with ultrasound has not yet been established in routine clinical practice, even though individual studies have shown that it is practicable with a good success rate 2–5 . Minimizing radiation dose is desirable, especially in young people.…”
Section: Introductionmentioning
confidence: 99%
“…The 8-3 MHz probe was used most frequently. While maintaining the supine position, the superior vena cava vein (SVC) and right atrium (RA) were visualized using ultrasound from four different positions (Figure 1A), three of which were described by Baehner et al 2 in a previous feasibility study, as follows:…”
mentioning
confidence: 99%